การสร้างตัวแบบกองทุนบำนาญแบบผสม - พิทูร เลียมจรัสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The objectives of the study is, generating the appropriate hybrid pension fund model by comparing the fund value between Defined Benefit (DB), Defined Contribution (DC) and a Hybrid Pension fund, Defined Benefit Underpin (DBU), subject to these factors which are an age of retirement, size and age structure. The study has used 8.9 million data of insured persons from the Social Security Fund (SSO) as of December 2010. Then, generate the dummy companies and its employee data from the model. The frame of a study is separated by 2 ideas, the overview of 3 types of pension funds; DB, DC and DBU pension, and the best strategy of the dummy companies which are Entry Age Normal (EAN), Projected Unit Credit (PUC) and the Traditional Unit Credit (TUC).The results of research found that, in next decade, the hybrid pension fund will give benefit to insured persons equal DB and more than DC, respectively. In case of dummy companies, the Projected Unit Credit (PUC) will be the best capital accumulation strategy for every company size (small, medium and large). Furthermore, the extension of retirement age affects the increasing value of a hybrid pension fund. Finally, if the retirement age has been limited, the company should increase a proportion of youth employees.